Consumer purchase intention towards global automobile brands in Malaysia / Sharinee Masrun - Masrun, Sharinee (2018)
National car brands are reported continuously declining in performance. On another note, imported car brands record increasing in unit sale year by year. This shows Malaysian consumers shift their purchase decision from national automobile brands to global automobile brands. The purpose of this study is to implore the factors has made Malaysians switch their intention from national automobile brands to global automobile brands. To attain the objectives of this study, research questions are developed and tested. Besides, literature reviews are included in this research as to provide better understanding towards consumer purchase intention on global automobile brands in Malaysia. Primary data were collected by administrating online questionnaire to 327 consumers in every state of Malaysia to test three hypotheses concerning the factors influencing Malaysian consumers purchase global car brands. The target population consists of global automobile brands who are working in public and private sector, self-employed and students. Those target population is purposely selected as they might be one of user, customer or prospect of global automobile brands in Malaysia. This study uses Statistical Package for Social Sciences (SPSS) version 24.0 and the data confirmed that the purchase intent of consumers towards global automobile brands is mainly affected by their preference on global brands. Practical implications of how this study can contribute to industry, future study and consumers; research limitations and recommendations for future studies are well explained in the final chapter of this study.